THE ROLE OF SELF-REGULATION IN LANGUAGE LEARNING (Modern education and development, 2025)
This article explores the importance of self-regulation in the process of learning a foreign language. It highlights how learners who are able to set goals, manage their time, monitor their progress, and reflect on their strategies achieve better results. The article is based on theoretical frameworks such as Zimmerman’s self-regulated learning model and Oxford’s taxonomy of language learning strategies. The findings suggest that fostering self-regulation leads to more independent, motivated, and successful language learners.